The Narrative Structure in the Poetry of Ibrahim ibn Yahya Abu Ishaq al-Ghazzi - Zweir, Hussam Jari (Thi Qar Arts Journal, 2025)
AbstractThe long writing on Al Ghazy’s Poetry. This study is refers to focus on important points that present in Abo Eshaq Al Ghazy’s poetry.He born in Al Abassy period and focus on the technics and if it deals on poetry.Al Ghazy can mix his poems with stories. He used the long writing as story